2013
DOI: 10.1590/s0104-530x2013000300013
|View full text |Cite
|
Sign up to set email alerts
|

Estado da arte das aplicações de curvas de aprendizado

Abstract: Curvas de aprendizagem permitem representar a melhoria no desempenho de um trabalhador por conta da repetição de um procedimento manual. Este artigo traz uma revisão da literatura das aplicações das curvas de aprendizado. Primeiramente, é apresentada uma breve revisão dos principais modelos de curva de aprendizado. É então apresentada uma revisão das principais utilizações para as curvas de aprendizado, agrupadas em 5 diferentes áreas de pesquisa: (i) Monitoramento de Custos; (ii) Gerenciamento e Otimização de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…The line is operated by the same staff since 2008, in contrast to C1 and C2 lines, where many employees changed sector or were dismissed. This distinction may have contributed to increased efficiency over time, considering the possibility of efficiency improvement by learning (Stroieke et al, 2013).…”
Section: Efficiency Analysis Of Production Linesmentioning
confidence: 99%
“…The line is operated by the same staff since 2008, in contrast to C1 and C2 lines, where many employees changed sector or were dismissed. This distinction may have contributed to increased efficiency over time, considering the possibility of efficiency improvement by learning (Stroieke et al, 2013).…”
Section: Efficiency Analysis Of Production Linesmentioning
confidence: 99%
“…Learning is useful to minimise costs of a new product insertion into the production process. Thus, a part of the research involving learning curves aims at optimising the performance of processes, improvement of the use of resources and reduction of processing costs (Stroieke et al, 2013). Studies (Levy, 1965; Li and Rajagopalan, 1997; Terwiesch and Bohn, 2001) revealed that the experience gained over time enables a company to produce more units in a particular time interval with reduced production costs.…”
Section: Introductionmentioning
confidence: 99%